Colombian regulation guidelines proposal for the rock blowing vibrations control in urban áreas. RCOLVV.09 (2017)
A preliminary guide appears for the regulation of vibrations generated by blasts in urban areas and their influence on the structures or the houses near the sites where the explosions take place. It refers torocks, grounds or materials with compressive strenghts average of 60 Mpa, that makes necessary the use of explosives for its fragmentation; which produces environmental alterations like vibrations, noise and projections that to generate annoyances to people and possible damages to their houses.